CURRICULUM DEVELOPMENT IN MADRASA: EXPLORATION FROM MUSLIM MINORITY OF WEST PAPUA - Wekke, Ismail Suardi (Jurnal Pendidikan Islam, 2016)
Muslim minority educational development was left behind to explore. The existing researches on the publication are only about Muslim majority. Therefore, it is a need to discover the existence of Muslim minority in the eastern part of Indonesia. This research was conducted in West Papua Province. In-dept interview and non-participant observation were conducted to collect data. Focus group discussion was circulated to ensure data triangulation. This study shows that environment neighborhood is one of the factors to consider in curriculum formation. Educational establishment is the breakthrough to fulfill the need of religious education. In addition, the standard to achieve is not only the national average but also there is vision to inaugurate social harmony and cultural situation. Finally, this article concludes that educational management board and teacher panel tried to perceive and hear the sound of milieu. This practice shows a progress of improvement and enhancement in improving relevant curriculum.